Biologia, capacidade de predação e morfologia de Stiretrus decastigmus (Herrich-Schaeffer, 1838), predador de Microtheca ochroloma Stal, 1860 - Poncio, Sônia (2012)
The objective of this study was to evaluate under laboratory conditions the best development stage of the prey (Microtheca ochroloma) for Stiretrus decastigmus; predator biology at different temperatures being M. ochroloma larvae offered, and predation on M. ochroloma larvae by S. decastigmus and Podisus nigrispinus nymphs were determined. Moreover, morphological description of S. decastigmus was performed. In the first test performed development of S. decastigmus preying on M. ochroloma larvae and/or adults was determined. The insects used to S. decastigmus biological aspects assess were maintained at three different temperatures (20, 25 and 30°C). The eggs were placed in Petri dishes and, after hatching, the nymphs were kept on the plates until they reached the second stage, when they were individually placed in plastic pots and fed on M. ochroloma larvae. The parameters evaluated were: incubation period and egg viability, duration and viability of the nymphal period. Also the ability of S. decastigmus predation was evaluated, compared with other pentatomid predator, P. nigrispinus. Larvae and adults of M. ochroloma were suitable for S. decastigmus nymphs development, however, the highest nymphal viability (85%) occurred when these fed only on M. ochroloma larvae. Incubation of bug eggs decreased with increasing temperature (five days at 30°C) and the highest eggs viability was at 25 °C (95%). The nymphal stage was lower at higher temperature (18 days at 30 ° C) and nymphal viability was higher at 25 °C (85%). The largest amount of eaten larvae (90.40) was performed by nymphs created at 20°C. Although P. nigrispinus have developed faster (19 days) and preyed more larvae (63), S. decastigmus showed the highest total survival (82%). Moreover morphological description of the egg, nymph and adult stages of S. decastigmus were done. According to biological parameters, it is concluded that S. decastigmus is a predator which shows favorable possibilities for use in M. ochroloma biological control.